Behavior and Health Indicators to Assess Cull Cow's Welfare in Livestock Markets - Sánchez-Hidalgo, Melissa; Bravo, Viviana; Gallo, Carmen (Frontiers in Veterinary Science, 2020)
The welfare status of cull cows going through livestock markets was assessed in 12 premises in Chile, using behavioral, health and handler indicators observed during unloading, auction and loading (once in winter and once in summer). Groups of cows were observed by the same observer and the following indicators were registered at each stage: slips, falls, balks, turns, jumps and vocalizations of cows were considered as negative behavioral events and a proportion was calculated based on the number of observed events per group divided by the number of cows per group to give a behavioral event index (BEI); health status of the cows was assessed during auction by registering the proportion of cows with low body condition, lameness, mammary gland problems, skin injuries and tail abnormalities; handler-behavior was assessed using a count of negative tactile interactions (NTI) with the cows, like blows/hits, kicks and pokes with the devices used to drive them, then a NTI index (NTII) was calculated as for BEI. Using the groups of cows as the statistical unit, multilevel model analyses were performed to identify variables associated with changes in BEI and NTII, using the software MLwiN 3.03. A total of 1,103 groups of cows (n=3,963 cows) were observed, finding a high percentage of slips and balks, whereas hitting and poking were frequent NTI. The highest mean BEI was observed during unloading in winter (1.10), whilst the lowest one was found during auction in summer (0.34). The NTII was highest during loading in winter (2.94) and lowest during auction in summer (0.23). There was an increase of 0.11 in BEI for every extra unit increase in the NTII by the handlers. The BEI was negatively affected by the winter season compared to summer. Of 1,608 cows, 49.8% had a low body condition, 28.3% had mammary gland problems, 24% were lame, 8.7% presented lesions and 3.1% tail abnormalities. It can be concluded that the health of the cull cows is already compromised when leaving the farms; cow behavior and handler tactile interactions with the cows are useful indicators to assess the welfare of cull cows at livestock markets.